Analysis of the Effectiveness of Internal Control on Debt Payments at Hotel "X" - Lim, Cheryl; Damayanti, Titien; Arnawa, I Putu (Indonesian Journal of Banking and Financial Technology, 2024)
This research aims to describe internal control over debt payments to suppliers at Hotel "X". This research uses qualitative descriptive data analysis techniques and uses a triangulation test. Data collection in this research used interview, observation and documentation techniques. The results of this research indicate that the effectiveness of internal control over debt payments at Hotel "X" is very effective. There was one implementation of internal control elements that was not achieved, namely that internal parties were unable to communicate effectively, resulting in double posting of invoices due to missed communication. This was caused by the non-implementation of the Standard Operating Procedure (SOP) regarding notification of aging receivables which should have been carried out by purchasing which was actually carried out by receiving. Socialization regarding Standard Operating Procedures (SOP) must be carried out regularly so that implementation can be maximized.